Migration Behavior of Immunoglobulin Y in Native Page Electrophoresis - Umul Karimah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
ABSTRACT Protein separation with electrophoresis in native state (native Polyacrylamide Gel Electrophoresis, native PAGE) is rarely applied in laboratory which results in limited scientific report. Native PAGE result can be used in further assay analysis or shows important protein-protein interaction. This study aimed to investigate immunoglobulin Y(IgY) behavior in separation using native PAGE. IgY protein is used since many properties of IgY are already known. IgY was isolated from follicles yolk and examined using clear native PAGE (CN-PAGE) and Sodium Dodecyl Sulphate (SDS) PAGE, both in reducing and nonreducing condition. CN-PAGE electropherogram of IgY showed streaked band from 409-1048 kDa indicating IgY aggregation. Whereas SDS-PAGE in reducing condition showed normal result, 68 kDa and 18,7 kDa protein bands correlated with heavy and light chain of IgY respectively. Moreover SDS PAGE in nonreducing condition also resulted in normal IgY band sized 185 kDa. Dilution and disaggregation using sodium dodecyl sulphate (SDS), sodium deoxycholate (SDC), sarcosyl, urea, and glycerol did not affect the migration behavior. We concluded that IgY is not in aggregate form. Migration behavior of IgY in CN-PAGE which was slow, produced streaked band, and appeared to have very high molecular weight is possibly due to low electronegativity (pI = 6,6±0,9) in CN-PAGE condition (buffer pH 8,3) and planar conformation of IgY. Keywords: electrophoresis, immunoglobulin Y, native PAGE.